Secondary prevention measures in anaphylaxis patients: Data from the anaphylaxis registry. Issue 4 (21st October 2019) - Kraft, Magdalena; Knop, Macarena Pia; Renaudin, Jean‐Marie; Scherer Hofmeier, Kathrin; Pföhler, Claudia; Bilò, Maria Beatrice; Lang, Roland; Treudler, Regina; Wagner, Nicola; Spindler, Thomas; Hourihane, Jonathan O'B; Maris, Ioana; et al.
Abstract: Background: Patients with a history of anaphylaxis are at risk of future anaphylactic reactions. Thus, secondary prevention measures are recommended for these patients to prevent or attenuate the next reaction. Methods: Data from the Anaphylaxis Registry were analyzed to identify secondary prevention measures offered to patients who experienced anaphylaxis. Our analysis included 7788 cases from 10 European countries and Brazil. Results: The secondary prevention measures offered varied across the elicitors. A remarkable discrepancy was observed between prevention measures offered in specialized allergy centers (84% of patients were prescribed adrenaline autoinjectors following EAACI guidelines) and outside the centers: Here, EAACI guideline adherence was only 37%. In the multivariate analysis, the elicitor of the reaction, age of the patient, mastocytosis as comorbidity, severity of the reaction, and reimbursement/availability of the autoinjector influence physician's decision to prescribe one. Conclusions: Based on the low implementation of guidelines concerning secondary prevention measures outside of specialized allergy centers, our findings highlight the importance of these specialized centers and the requirement of better education for primary healthcare and emergency physicians. Abstract : Data from the Anaphylaxis Registry were analyzed to identify secondary prevention measures offered to patients who experienced anaphylaxis. In specialized allergy centers 84% of patients were prescribed adrenaline autoinjectors following EAACI guidelines and only 37% outside the centers. The secondary prevention measures offered to the anaphylaxis patients varied with the elicitor, and to some extent with other factors such as patients' age, comorbidities, and reaction severity. Abbreviation: AAI, adrenaline autoinjector